Metode Pengajaran Veda pada Anak Usia Dini - Surpi, Ni Kadek (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2017)
In Hinduism, education begins in the Mother’s womb. However, in relation to CaturAsrama (four stages of human life), education begins at the age of 0-25 years to be able to move to the next level. Vedic education can be done in early childhood as the general definition that children aged 0 years to 6 years. In principle, Vedic teaching can be done at any age, but with different methods. A number of popular methods have been practiced in Vedic teaching since ancient times such as Katha, Gatha, Narasamsi, Mantra, repetition, role- playing and various other methods that can be adapted to local conditions. However, the Vedas are loaded with the teachings of wisdom, truth, and courage must be taught from an early age and further strengthened as adolescence and adulthood. Vedic teaching involves a holistic teaching system that builds people from within and enhances intellectual, emotional as well as spiritual intelligence to build superior and divine human beings as the Vedic ideals.